Role of the cystathionine β-synthase / H2S pathway in the development of cellular metabolic dysfunction and pseudohypoxia in down syndrome - Theodora Panagaki; Laszlo Pecze; Elisa B. Randi; Anni I. Nieminen; Csaba Szabo (Redox Biology, 2022)
Background: Overexpression of the transsulfuration enzyme cystathionine-β-synthase (CBS), and overproduction of its product, hydrogen sulfide (H2S) are recognized as potential pathogenetic factors in Down syndrome (DS). The purpose of the study was to determine how the mitochondrial function and core metabolic pathways are affected by DS and how pharmacological inhibition of CBS affects these parameters. Methods: 8 human control and 8 human DS fibroblast cell lines have been subjected to bioenergetic and fluxomic and proteomic analysis with and without treatment with a pharmacological inhibitor of CBS. Results: DS cells exhibited a significantly higher CBS expression than control cells, and produced more H2S. They also exhibited suppressed mitochondrial electron transport and oxygen consumption and suppressed Complex IV activity, impaired cell proliferation and increased ROS generation. Inhibition of H2S biosynthesis with aminooxyacetic acid reduced cellular H2S, improved cellular bioenergetics, attenuated ROS and improved proliferation. 13C glucose fluxomic analysis revealed that DS cells exhibit a suppression of the Krebs cycle activity with a compensatory increase in glycolysis. CBS inhibition restored the flux from glycolysis to the Krebs cycle and reactivated oxidative phosphorylation. Proteomic analysis revealed no CBS-dependent alterations in the expression level of the enzymes involved in glycolysis, oxidative phosphorylation and the pentose phosphate pathway. DS was associated with the dysregulation of several components of the autophagy network; CBS inhibition normalized several of these parameters. Conclusions: Increased H2S generation in DS promotes pseudohypoxia and contributes to cellular metabolic dysfunction by causing a shift from oxidative phosphorylation to glycolysis.